ANALISIS JUAL BELI DENGAN MENGGUNAKAN AKAD MURABAHAH DI BANK SYARIAH (Studi Analisis Di Bank Syariah Indonesia Cabang Rantau Prapat) - Hudrah Dewiyana; Mustamam Mustamam; Adil Akhyar (LPPM YPITI, 2021)
The implementation of financing under the murabahah agreement is based on the Fatwa of the National Sharia Council of the Indonesian Ulama Council Number 04 / DSNMUI / IV / 2000 concerning Murabahah. The murabahah contract in question is selling an item by confirming the purchase price to the buyer and the buyer paying a higher price. The problem formula in this thesis is how to arrange the implementation of buying and selling using the murabahah contract in the perspective of Islamic law at Bank Syariah Indonesia Rantau Prapat, how the implementation of buying and selling using the murabahah contract in the perspective of Islamic law at Bank Syariah Indonesia Rantau Prapat, how are the solutions to external and internal obstacles in the implementation of buying and selling using the murabahah contract at Bank Syariah Indonesia Rantau Prapat. This type of research is a normative juridical research that is based on statute and empirical juridical research by conducting interviews with the Head of the Branch of Bank Syariah Indonesia Rantau Prapat. The data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. The conclusion in this paper is carried out using deductive-inductive thinking logic, which is done with the theory used as a starting point for conducting research. The results showed that the arrangement for the implementation of the murabahah contract carried out at Indonesian Sharia Bank is based on the Fatwa of the National Sharia Council of the Indonesian Ulama Council Number 04 / DSN-MUI / IV / 2000 concerning murabahah. The implementation of the murabahah contract at Bank Syariah Indonesia is a financing provided by banks to prospective debtor customers to finance their business needs through working capital financing, investment, people's business credit (KUR), bud, middle and main financing by using the murabahah contract as the financing agreement contract. . Barriers to Implementation of Murabahah Agreement at Indonesian Sharia Bank are customers do not carry out their payment / payment obligations on the agreed time, documents or information submitted by the customer to the bank are fake, invalid, or incorrect.